The role of e-learning in open distance learning : a case study of a selected institution - Mabasa, Tlhanyi Olga; Baloyi, Gezani Phineas (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
A qualitative approach was used to study the role of eLearning in Open Distance Learning at Unisa. This is an exploratory study. The importance of Open Distance and eLearning has motivated the researchers to embark on the study. For this limited scope dissertation, the researcher physically interviewed ten students selected using purposive sampling. The participants were limited to Unisa students enrolled in the College of Education. Participants were selected based on their experience in ODeL mode of learning. The data was analysed, presented, coded, organised, categorised and themes were identified. The findings suggest that participants understood student support in the context of ODeL. The responses revealed that ODeL reduces costs, is a flexible, enriched learning experience, increases success rate and encourages life-long learning for all age groups and cultures. The ODeL module should continuously be improved to remain credible. It is important to note that this paper could not address all issues of student support in ODeL. Although the participants were a small sample, it is believed that the findings of this study make a valuable contribution to eLearning in Open Distance Learning. Student monitoring, and effective mechanisms to curb internet access challenges for online students can ensure success. Furthermore, the findings revealed that students need to be taught computer literacy before registering for this specific online module
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 1, Volume 9, 2025
Keywords: Digital learning; Internet; Online learning; Open Distance and eLearning; Technology; GALILEO (Information retrieval systems); Distance learning; Open learning; Educational technology